1996
DOI: 10.1093/nar/24.10.1837
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of a unique thymine-thymine dimer or thymine-thymine pyrimidine pyrimidone (6-4) photoproduct in mammalian cells

Abstract: The mutagenic properties of UV-induced photoproducts, both the cis-syn thymine-thymine dimer (TT) and the thymine-thymine pyrimidine pyrimidone (6-4) photoproduct [T(6-4)T] were studied in mammalian cells using shuttle vectors. A shuttle vector able to replicate in both mammalian cells and bacteria was produced in its single-stranded DNA form. A unique photoproduct was inserted at a single restriction site and after recircularization of the single-stranded DNA vector, this latter was transfected into simian CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 27 publications
5
52
0
Order By: Relevance
“…This is consistent with the results that we have previously obtained with nonreplicating gapped plasmids in mammalian cells (28,41) and with an earlier report using a replicative plasmid (42). A recent study reported that TLS across a TT 6-4 PP in a replicating plasmid is largely accurate (43).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with the results that we have previously obtained with nonreplicating gapped plasmids in mammalian cells (28,41) and with an earlier report using a replicative plasmid (42). A recent study reported that TLS across a TT 6-4 PP in a replicating plasmid is largely accurate (43).…”
Section: Discussionsupporting
confidence: 93%
“…A recent study reported that TLS across a TT 6-4 PP in a replicating plasmid is largely accurate (43). This difference does not stem from a replicative vs. a gapped nonreplicating plasmid as those authors suggested, because an earlier study using a replicative plasmid found that TLS is highly mutagenic (42), like in our study. The reason for the difference is not known yet, but it should be pointed out that the TLS that we have monitored across chromosomal TT 6-4 PP was highly mutagenic.…”
Section: Discussionsupporting
confidence: 78%
“…Most notably, an elevated UV-induced skin cancer proneness has been found for XPCÀ/À mice (29), which are TCR proficient and differ from the WT mice by the absence of 6-4PP GGR (20). In this respect, it is worth noting that mutagenic bypass of 6-4PPs in mammalian cells has been reported to be >10 times higher than for CPDs (46). The similar delay in repair of 6-4PPs in both human and mouse cells deficient for DDB2 suggests that the accelerating role of DDB2 in 6-4PP repair might also be important in the protection of humans against UV-induced skin cancer.…”
Section: Ddb2 Protects Mice From Uv-induced Skin Cancermentioning
confidence: 99%
“…2). However, most of the UV-induced mutations at TT sequences are T-A-to-C-G transitions at the 3Ј T-A base pair (19,32). Therefore, in addition to the 5Ј T-G mismatches in our TϽϾT compound lesions, we wished to use 3Ј T-G-associated compound lesions to ascertain that the preferential repair of compound TϽϾT lesions contributes to UV mutagenesis.…”
Section: Fig 1 Incision/excision Of Tͻͼt and T[6-4]t Photoproducts mentioning
confidence: 99%